Changing trends and the impact of alcohol on the HIV/AIDS epidemic in South Africa: Review - Mashiko Setshedi; Suzanne M de la Monte (Taylor & Francis Group, 2011)
The association between increased HIV infection and alcohol use has been extensively studied and is established. South Africa is among one of the sub-Saharan African countries with the highest prevalence and number of people living with HIV/AIDS in the world. Although recent evidence suggests that the epidemic has stabilised, infection rates remain unacceptably high. Alcohol use is on the increase, particularly in the groups most susceptible to HIV infection, namely women and young adults, and informs poor choices with respect to safer sexual practices. This paper reviews the association between alcohol and HIV. More specifically, however, it aims to explore the potential socio-politico-biological and cultural explanations as to the factors that intersect to drive these two epidemic diseases: alcoholism and HIV/AIDS in South Africa. Understanding some of the underlying factors will provide a framework to implement public health measures to curb HIV.